Analisis Integrasi Metode Quality Risk Management dan Hoshin Kanri Sebagai Upaya Peningkatan Produktivitas - Ar Rafli, Ferdiansyah; Prabowo, Rony (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2024)
Quality is the level of the inherent character of a product. One of the company's efforts is to produce quality products that consumers want while still managing risks that can affect the quality of each product. But the company still finds products that do not meet standard specifications, Quality Risk Management is carried out to identify risks through brainstorming and analyzing, and determining what factors can cause product defects and managing risks using the House of Risk to reduce risks that occur, and 29 risk agents cause the product does not meet specifications and 14 preventive actions as mitigation measures. At Hoshin, Kanri produces efforts to achieve company goals by providing improvement suggestions, Targets to Improve-Top level Improvement-Annual Objectives-3-5year Breakthrough Objectives.